The Booklet Development of Inorganic Fertilization System Based on Problem - M. A. Y. Nirmalasari; Yovita Y. Bolly (Universitas Tadulako, 2020)
The use of inorganic fertilizer in the tillage was mostly used by Sikkanese. The reason was the large supply of inorganic fertilizer on the market, fast response, easy to absorb, and not to waste times. In the implementation, inorganic fertilizer was not used accordance with the stipulation of the four rights (4T): right dose, right time, right place, and right source. The result was the decrease of soil quality and the death of soil-degrading microorganisms so that the soil became infertile. Therefore, the booklet as a learning media gave the right information about the proper fertilization system. The research aims to know the appropriateness of the booklet development of inorganic fertilization system. The method used was the research and development (R n D) method by adopting a Borg and Gall model. The sample was taken by using purposive sampling. The analysis technical was validity analysis (valid percentage) and appropriate analysis (Widoyoko categorial). The result of the study showed that the booklet was appropriated to use as a medium of information for the farmer with the feasibility category both at the initial field trial and field trial stages. Furthermore, in the field trial implementation, the booklet was suitable to use with the very good feasibility category.